Systematization of the prospective analysis of the Ecuadorian military industrial system - Angie Fernández Lorenzo; Humberto Aníbal Parra Cárdenas; Darwin Manolo Paredes Calderón (Cooperativismo y Desarrollo, 2023)
This article provides a systematic analysis of the dynamics of the actors associated with the defense industry in Ecuador, as one of the economic branches that has the best chance of boosting economic growth through contributions to the Gross Domestic Product, employment generation and the promotion of national production. The analysis was carried out with a prospective approach, applying the quintuple helix innovation model that allows an integral analysis from the economic, social and environmental components to address a topic of great interest for Ecuador. The research methods applied were historical, systemic, dialectical and modeling, supported by procedures such as analysis-synthesis and integration-abstraction. In particular, a comparative analysis was carried out between Ecuador and other countries in the region, which made it possible to determine common aspects and gaps, especially with Brazil, Latin America's leading country in this area. The development of the research project summarized in the article will allow laying the foundations for decision making in the sector focused mainly on two variables: investment policies and the management model to be implemented that will allow dynamizing the participation of the different public and private actors in the development of the Ecuadorian defense industry system.